Percutaneous closure of aortic pseudoaneurysm in a young female with atrial septal occluder - Deshpande, Shantanu (J Cardiol Cases, 2016)
This case report represents a novel technique for the treatment of a pseudoaneurysm of the aorta. Pseudoaneurysm of the aorta has been reported in patients post heart surgery. This case report is about a patient who had a pseudoaneurysm most probably following tuberculosis. Traditionally, the treatment of choice is surgical correction; however, in the current era, there are case reports describing the use of either stent grafts or Amplatzer occluders for occlusion of the pseudoaneurysm in high-risk surgical cases. We performed successful closure of the aortic pseudoaneurysm using atrial septal occluder. <Learning objective: Tuberculous arteritis can result in pseudoaneurysm rarely. Our patient had a large aneurysm compressing adjoining vital structures and was very high surgical risk case. This is the first case report of closure of tuberculous pseudoaneurysm by using atrial septal occluder in a young patient. In this case we have demonstrated that large pseudoaneurysms with narrow neck can be closed very safely using atrial septal occluder with immediate symptom relief and thrombosis of pseudoaneurysm at follow-up of three months.>